A Comprehensive Study on Tetraaryltetrabenzoporphyrins. Issue 15 (6th February 2020) - Ruppel, Michael; Lungerich, Dominik; Sturm, Sabrina; Lippert, Rainer; Hampel, Frank; Jux, Norbert
Abstract: Tetraaryltetrabenzoporphyrins (TATBPs) show, due to their optoelectronic properties, rising potential as dyes in various fields of physical and biomedical sciences. However, unlike in the case of porphyrins, the potential structural diversity of TATBPs has been explored only to little extent, owed mainly to synthetic hurdles. Herein, we prepared a comprehensive library of 30 TATBPs and investigated their fundamental properties. We elucidated structural properties by X‐ray crystallography and found explanations for physical properties such as solubility. Fundamental electronic aspects were studied by optical spectroscopy as well as by electrochemistry and brought in context to the stability of the molecules. Finally, we were able to develop a universal synthetic protocol, utilizing a readily established isoindole synthon, which gives TATBPs in high yields, regardless of the nature of the used arylaldehyde and without meticulous chromatographic purifications steps. This work serves as point of orientation for scientists, that aim to utilize these molecules in materials, nanotechnological, and biomedical applications. Abstract : The underrepresented class of tetraaryltetrabenzoporphyrins (TATBPs) is investigated thoroughly by DFT calculations, X‐ray diffraction, optical spectroscopy, electro‐ and photochemical studies. Fundamental and unexpected insights were gained about structural and electronic properties of this compound class, which will advance the research around TATPBs based technologies, such as in materials and life sciences.